Esophageal Retained Lithium Battery in Children Younger than 6 Years: A Prompt Structured Multidisciplinary Approach Is Essential to Reduce Long-Term Consequences. Issue 6 (June 2021) - Lisi, Gabriele; Illiceto, Maria Teresa; Romeo, Erminia Francesca; Lauriti, Giuseppe; Faraci, Simona; Lombardi, Giuliano; Dall'Oglio, Luigi; Chiesa, Pierluigi Lelli
Abstract : Objectives: Disk battery esophageal retention in children younger than 6 years represents an increasing endoscopic emergency, followed by a relevant risk of life-threatening late complications. Surgical removal after a failed endoscopic approach is rarely reported in the literature. We describe our experience in this scenario. Methods: Two female asymptomatic patients aged 26 and 29 months presented within 4 hours after a witnessed ingestion of a 2-cm, 3-V lithium battery (CR2032) retained in the cervical esophagus. Both patients underwent a prolonged unsuccessful emergent endoscopic removal with a flexible instrument performed by an adult gastroenterologist. Both batteries fused with the esophageal wall were extracted through a longitudinal left cervical esophagotomy combined with minimal resection of necrotic tissues and repaired over a 12F feeding tube. Results: Patients were extubated after 12 and 72 hours, respectively. Contrast study was performed after 20 and 13 days, respectively, before resuming oral feeding. At endoscopy, the first patient developed a 3-cm-long severe esophageal stenosis (35th day), followed by an asymptomatic tracheoesophageal fistula (60th day), which was conservatively treated. After spontaneous resolution of the tracheoesophageal fistula, esophageal stenosis progressed, partially responsive to esophageal stenting. Short esophagectomy is under evaluation. The second patient developed an asymptomatic limited stenosis, not requiring dilatation. Conclusions: The emergent management of lithium battery ingestion needs a structured timely multidisciplinary approach in the emergency department, an experienced pediatric endoscopist, and a simultaneous engagement of pediatric surgical expertise, even in patients who do not show bleeding, to reduce esophageal exposure time to high-voltage current released by batteries, which represents the main factor conditioning tissue damage and prognosis.